Emerging analytical techniques for analysis of pesticides - Yahaya, Noorfatimah; Mohamad Zain, Nur Nadhirah; Miskam, Mazidatulakmam; Kamaruzaman, Sazlinda; Mohamed, Ahmad Husaini (Elsevier, 2024)
Due to the increasing population and the need to produce safe foods to feed the growing population, food safety is one of the most important global issues. The presence of pesticide residues in agricultural products may pose a significant threat to food safety because most pesticides are harmful at certain concentration levels when expose to humans. The applications of herbicides, fungicides, insecticides, and pesticides have resulted in increased crop output. However, their chemical, physical and biological properties such as toxicity, stability, polarity, bioaccumulation, and water solubility make them among the most toxic compounds that pollute the environment. Uncontrol usage and exposure to minute amounts of concentration of pesticides especially from vegetables, fruits, and food matrices may lead to food chain contaminations. Thus, continuous monitoring of pesticide residues in food matrices is critical to protect the lives of humans and other organisms in the ecosystem. As the direct determination of pesticides is challenging due to their trace levels in food matrices, several strategies in the development of analytical techniques and sample preparation have been designed to enhance the sensitivity, selectivity, accuracy, and precision of the developed method. Based on different techniques, the chapter is organized into four sections that include green sample preparation, chromatography or mass spectrometry techniques, capillary electrophoresis, and spectrophotometry techniques for analyzing pesticides in food matrices. This chapter will provide valuable insight to food analysts and regulatory authorities in standardizing quality indicator parameters during analyses and formulating suitable measures to maintain the security, quality, and safety of fresh food products. This chapter presents a review of published works from 2018 onwards on the topic related to the analytical techniques for quantifying pesticides in food matrices.